How do you find #dy/dx# by implicit differentiation given #x^2+3xy+y^2=0#?

Answer 1
Given: #x^2+3xy+y^2=0#

Differentiate each term with respect to x:

#(d(x^2))/dx + (3d(xy))/dx+ (d(y^2))/dx=(d(0))/dx#
Use the power rule, #dy/dx = nx^(x-1)#, on the first term:
#2x + (3d(xy))/dx+ (d(y^2))/dx=(d(0))/dx#
Use the product rule, #(d(xy))/dx= dx/dxy+xdy/dx = y + xdy/dx# on the second term:
#2x + 3(y + xdy/dx)+ (d(y^2))/dx=(d(0))/dx#
Use the chain rule, #(d(y^2))/dx=2ydy/dx#, on the third term:
#2x + 3(y + xdy/dx)+ 2ydy/dx=(d(0))/dx#

The derivative of a constant is 0:

#2x + 3(y + xdy/dx)+ 2ydy/dx=0#

Distribute the 3:

#2x + 3y + 3xdy/dx+ 2ydy/dx=0#
Move all of the terms that do not contain #dy/dx# to the right:
#3xdy/dx+ 2ydy/dx=-(2x+3y)#
Factor out #dy/dx#:
#(3x+2y)dy/dx=-(2x+3y)#
Divide by #3x+2y#:
#dy/dx=-(2x+3y)/(3x+2y)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

#dy/dx=-(2x+3y)/(3x+2y)#

#"differentiate "color(blue)"implicitly with respect to x"#
#"the term " 3xy" is differentiated using the "color(blue)"product rule"#
#rArr2x+3(x.dy/dx+y.1)+2y.dy/dx=0#
#rArr2x+3xdy/dx+3y+2ydy/dx=0#
#rArrdy/dx(3x+2y)=-2x-3y#
#rArrdy/dx=-(2x+3y)/(3x+2y)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

#(dy)/(dx)=-1/2(sqrt 5 pm 3)#

From #x^2 + 3 x y + y^2=0 -> y = -1/2(sqrt 5 pm 3)x#

then

#(dy)/(dx)=-1/2(sqrt 5 pm 3)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 4

To find ( \frac{dy}{dx} ) by implicit differentiation for the equation ( x^2 + 3xy + y^2 = 0 ), follow these steps:

  1. Differentiate both sides of the equation with respect to ( x ).
  2. Use the chain rule where necessary.
  3. Isolate ( \frac{dy}{dx} ) on one side of the equation.

The steps are as follows:

  1. Differentiating both sides of the equation:

[ \frac{d}{dx}(x^2) + \frac{d}{dx}(3xy) + \frac{d}{dx}(y^2) = \frac{d}{dx}(0) ]

  1. Applying the product rule for ( 3xy ):

[ 2x + 3\frac{dy}{dx} + 3y + 2y\frac{dy}{dx} = 0 ]

  1. Rearranging terms and isolating ( \frac{dy}{dx} ):

[ (3\frac{dy}{dx} + 2y) + (2x + 3y\frac{dy}{dx}) = 0 ] [ 3\frac{dy}{dx} + 2y + 2x + 3y\frac{dy}{dx} = 0 ] [ 3\frac{dy}{dx} + 3y\frac{dy}{dx} = -2y - 2x ] [ \frac{dy}{dx}(3 + 3y) = -2y - 2x ] [ \frac{dy}{dx} = \frac{-2y - 2x}{3 + 3y} ]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7